Evaluation of the books of Islamic education for the higher elementary stage in Jordan in the light of contemporary professional education standards - Abu Ghalioun, Eid Ismail Abed Rabbo (Journal of Educational and Psychological Sciences, 2018)
The study aimed at uncovering the standards of contemporary professional education, including books of Islamic education for the higher elementary stage in Jordan. The descriptive method based on the method of content analysis was used. The sample of the study consisted of the same study society, namely the Islamic Education textbooks for the higher elementary stage issued by the Ministry of Education for the academic year 2017/2018, which is taught in all the schools of the Hashemite Kingdom of Jordan. The study included five axes that included 30 contemporary professional standards. The results of the study revealed the low availability of contemporary professional standards in these books. Where the fifth axis (household science) ranked first, with repetitions (167) times, and by (26.55%), which is high, and the axis (agricultural) ranked second, repeating (160), and (25.43% , Followed by (Commercial), followed by (136), and (21.62%), which is medium. The Industrial (Industrial) came in fourth place with 88 recurrences, with 13.99% (Health and Safety) ranked fifth with 78 recurrences and 12.40%, which is also low. In light of the results of the study, the researcher recommended the inclusion of the professional dimension in the books of Islamic education for the higher elementary stage in Jordan by introducing professional information and concepts, or linking the content with appropriate subjects and professional issues.